2000
DOI: 10.1210/endo.141.7.7571
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Selenium Deficiency on Tissue Selenium Content, Deiodinase Activity, and Thyroid Hormone Economy in the Rat during Development*

Abstract: The iodothyronine deiodinases, D1, D2, and D3, all contain selenium (Se) in the form of selenocysteine at their active sites, and they play crucial roles in determining the circulating and intracellular levels of the active thyroid hormone (TH), T3. However, not only are serum T3 levels normal in Se-deficient rats but phenotypic and reproductive abnormalities are minimal, and it has been suggested that regulatory mechanisms exist to conserve Se in critical tissues. The present study was designed to determine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(31 citation statements)
references
References 53 publications
(35 reference statements)
3
22
0
4
Order By: Relevance
“…Wichtel et al (1996) showed that the plasma concentration of total thyroxin was increased (P<0.001) by selenium treatment and Bik (2003) determined the effect of selenium and iodine oral supplements on the concentration of T 3 and T 4 in the serum of sheep. It is important to note that only when selenium levels decreased by more than 80%, deiodinase activity was markedly decreased (Bates et al 2000). Bates et al (2000) stated that with the exception of liver, skin and nonpregnant uterus, all of the tissues studied (including cerebrum, thyroid, pituitary, brown adipose tissue, ovary, testes and placenta) maintained substantial deiodinase activity (>50%) during prolonged selenium deficiency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wichtel et al (1996) showed that the plasma concentration of total thyroxin was increased (P<0.001) by selenium treatment and Bik (2003) determined the effect of selenium and iodine oral supplements on the concentration of T 3 and T 4 in the serum of sheep. It is important to note that only when selenium levels decreased by more than 80%, deiodinase activity was markedly decreased (Bates et al 2000). Bates et al (2000) stated that with the exception of liver, skin and nonpregnant uterus, all of the tissues studied (including cerebrum, thyroid, pituitary, brown adipose tissue, ovary, testes and placenta) maintained substantial deiodinase activity (>50%) during prolonged selenium deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that only when selenium levels decreased by more than 80%, deiodinase activity was markedly decreased (Bates et al 2000). Bates et al (2000) stated that with the exception of liver, skin and nonpregnant uterus, all of the tissues studied (including cerebrum, thyroid, pituitary, brown adipose tissue, ovary, testes and placenta) maintained substantial deiodinase activity (>50%) during prolonged selenium deficiency. Although the ability of a tissue to maintain deiodinase activity in the face of dietary selenium deprivation was associated in some tissues with a concomitant local preservation of selenium concentration, this was not the case for all tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon severe selenium deficiency, hepatic D1 activity in rat is decreased, although liver selenium levels and D1 activities do not tightly correlate [34]. In addition, in severely selenium deficient rats the drastically reduced hepatic D1 activities were not reflected in the moderate changes measured in thyroid hormone levels [35 -37].…”
Section: Discussionmentioning
confidence: 99%
“…The enzymatic activity of 5MI has a strong inverse relationship to selenium deficiency [8]. Low selenium concentration effects in thyroid hormone levels can be completely reversed after selenium supplementation with sodium selenite [9].…”
Section: Introductionmentioning
confidence: 99%